The sputtering performance of Ag sputtering targets with different microstructure. (April 2023) - Ning, Zheda; Wang, Yiqing; Li, Sixie; Tang, Ke; Wen, Ming
Abstract : Ag thin films are widely used as the key material for electronic industries, and magnetron sputtering has become a general approach for Ag thin films deposition by using Ag targets as source materials. The microstructure of targets could affect the thin films thus sputtered. In our research, the sputtering performance of Ag targets in cold rolling state and annealing state was compared and the relationship between the Ag targets and Ag thin films were discussed. The results showed that annealing at 600 °C after cold rolling deformation of 83.33% can effectively increase the texture density of 110 in Ag. Both cold rolling state and annealing state Ag targets exhibit the similar deposition rate. The resistivity of both kinds of Ag thin films decreases with sputtering time. At the same sputtering time, the Ag thin films sputtered by annealing state Ag targets shows lower resistivity as compare with those sputtered by cold rolling state Ag targets. Due to the uniform microstructure of annealing state Ag target, it shows shallower depth of rack track after sputtering. Annealing treatment after cold rolling is an adaptable method to obtain optimized target microstructure. This knowledge could give some new ideas on the preparing of metal sputtering targets. Highlights: Larger plastic deformation and annealing treatment was developed to obtain uniform microstructure of Ag sputtering target. At the same sputtering time, the Ag thin films sputtered by annealing state Ag targets shows lower resistivity. Annealing treatment after cold rolling improved the utilization of Ag target.